Hands-On Cross-Platform Development with Xamarin. Forms - Liberty, Jesse (Packt Publishing, 2020)
Develop cross-platform apps with the help of Xamarin. Forms About This Video This course provides a complete tour of Xamarin. Forms, from an introduction to XAML right through to advanced Xamarin. Forms concepts and techniques The course is ordered logically, with each skill based on what has come before. The complete source code is available on GitHub to make following along easier. You will be using the very latest version of Xamarin. Forms and C# 8, allowing us to take advantage of the latest features In Detail This course will be your perfect guide and will help you get up-and-running with building cross-platform mobile applications with the Xamarin. Forms framework. You will learn about the basics of Visual Studio 19, how to download and install it, and Xcode. We will cover View Model concepts and explore Data Binding as well as event handlers. We use a practical and hands-on approach to help you understand NUnit and Moq concepts effectively. You will understand how Xamarin. Forms allow you to create user interfaces that can be shared across platforms. We start by running a program using both Android and iOS emulators and simulators, respectively. Then we will set up a solution for your cross-development project. Along the way, you will look at unit-testing your code. By the end of the course, you'll be confident enough to design and develop cross-platform applications with the help of Xamarin. Forms.
Online resource; Title from title screen (viewed May 21, 2020)
Keywords: Electronic videos